Comparative effects of biological and chemical dispersants on the bioavailability and toxicity of crude oil to early life stages of marine medaka (Oryzias melastigma). (16th September 2014) - Mu, Jingli; Jin, Fei; Ma, Xindong; Lin, Zhongsheng; Wang, Juying
Abstract The authors assessed the bioavailability and chronic toxicity of water‐accommodated fractions of crude oil (WAFs) and 2 dispersants plus dispersed crude oil (chemical dispersant + crude oil [CE‐WAF] and biological dispersant + crude oil [BE‐WAF]) on the early life stages of marine medaka, Oryzias melastigma. The results showed that the addition of the 2 dispersants caused a 3‐ and 4‐fold increase in concentrations of summed priority polycyclic aromatic hydrocarbons (PAHs) and high‐molecular‐weight PAHs with 3 or more benzene rings. The chemical and biological dispersants increased the bioavailability (as measured by ethoxyresorufin‐O‐dethylase activity) of crude oil 6‐fold and 3‐fold, respectively. Based on nominal concentrations, chronic toxicity (as measured by deformity) in WAFs exhibited a 10‐fold increase in CE‐WAF and a 3‐fold increase in BE‐WAF, respectively. When total petroleum hydrocarbon was measured, the differences between WAF and CE‐WAF treatments disappeared, and CE‐WAF was approximately 10 times more toxic than BE‐WAF. Compared with the chemical dispersant, the biological dispersant possibly modified the toxicity of oil hydrocarbons because of the increase in the proportion of 2‐ and 3‐ringed PAHs in water. The chemical and biological dispersants enhanced short‐term bioaccumulation and toxicity, through different mechanisms. These properties should be considered in addition to their efficacy in degrading oil when oil spill management strategies are selected. Environ Toxicol Chem 2014;33:2576–2583. © 2014 SETAC